Estimates for the entropy numbers of the classes B_p,θ^Ω of periodic multivariate functions in the uniform metric - Pozhars’ka, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish order estimates for the entropy numbers of the classes B_p,θ^Ω of periodic multivariate functions in the uniform metric. For the proper choice of the functions Ω, these classes coincide with the Nikol’skii – Besov classes B_p,θ^r.